Human Papillomavirus Genotypes Predict Progression of Anal Low-Grade Squamous Intraepithelial Lesions. (21st July 2018) - Liu, Yuxin; Sigel, Keith; Gaisa, Michael M
Abstract : Patients with anal low-grade squamous intraepithelial lesions who are positive for high-risk human papillomavirus (HPV), especially types 16/18, have an increased risk of developing high-grade squamous intraepithelial lesions. Type-specific HPV testing could serve as a risk stratification tool, providing prognostic information. Abstract: Background: High-risk human papillomavirus (hrHPV)–induced anal low-grade squamous intraepithelial lesions (LSILs) have the potential to progress to high-grade squamous intraepithelial lesions (HSILs). We investigated whether anal hrHPV infections, particularly types 16 and 18, predict LSIL-to-HSIL progression. Methods: One hundred forty-six human immunodeficiency virus (HIV)–infected and 22 HIV-uninfected patients with anal LSILs underwent cytology, HPV genotyping (16, 18, and pooled 12 hrHPV types), and high-resolution anoscopy-guided biopsy at baseline and surveillance. The associations between the rate of LSIL-to-HSIL progression and HPV types as well as longitudinal HPV-16/18 status were assessed by fitting separate Cox regression models. Results: At baseline, 91% of patients harbored hrHPV: HPV-16/18 (44%) and non-16/18 (86%). Upon follow-up (median, 20 [range, 6–36] months), 41% developed HSIL (84% at the same anatomic location as the initial LSIL and 16% at a different location). Baseline HPV-16/18–positive patients had greater probability of progression than patients with non-16/18 types or negative (67%, 25%, and 7%, respectively; P < .001). Persistent HPV-16/18 conferred the highest probability of progression (70%), followed by intermittent HPV-16/18 positivity (52%). In unadjusted and adjusted analyses, baseline and persistent HPV-16/18 were significantly associated with LSIL-to-HSIL progression. Conclusions: Anal LSIL patients who are positive for hrHPV, especially HPV-16/18, have an increased risk of developing HSIL. Type-specific HPV testing could serve as a risk stratification tool, providing prognostic information.